The Connection of Ahmed Benyoucef El Miliani with the Youssoufia Heresy Community through the Historical Sources (First quarter of the 10th Century AH / 16th Century AD) - amari, fatiha; fkair, abdelkader (The Algerian Historical Journal, 2026)
This paper addresses the relation and link between one of the most prominent Sufis in modern times, who is Cheikh Ahmad Ben Yousef El Rachidi El Meliani, from the Youssoufi Sect, who claimed Sufism. The latter first rose in Morocco during the first quarter of the 10th century A.H/16 A.D, it was considered one of the biggest Bid’ah (heretical doctrines); This is based on what was mentioned in the sources. The relation at hand regards that the Yousoufis who exaggerated their horrible practices, and went against jurisprudential rulings and overall Sufism, have practiced their Bid’ah as though it was amongst the rulings of Cheikh El Meliani. They have even confessed their affiliation to him and considered themselves an extended branch from his Rachidi ways. Despite their claims, we find that the Cheikh is innocent from their affiliation, which is evident in historical sources.